2023
DOI: 10.3390/microorganisms11102453
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotics in New-Born and Children’s Health

Shanmugaprakasham Selvamani,
Nidhi Kapoor,
Arun Ajmera
et al.

Abstract: At present, prebiotics, like probiotics, are receiving more attention as a promising tool for health maintenance. Many studies have recognized the role of prebiotics in preventing and treating various illnesses including metabolic disorders, gastrointestinal disorders, and allergies. Naturally, prebiotics are introduced to the human body in the first few hours of life as the mother breastfeeds the newborn. Prebiotic human milk oligosaccharides (HMOs) are the third largest constituent of human breastmilk. Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 111 publications
(300 reference statements)
1
3
0
Order By: Relevance
“…Regarding the HMDB annotation of some metabolites found in this work, B-trisaccharide is a metabolite found in a variety of animal-derived foods. A previous study has found this substance in urine after galactose administration [90], and it might also be a prebiotic (HMO) present in HM [91]. Neocasomorphin, found in our HM samples, is a casein-derived peptide with opioid function [92].…”
Section: Discussionsupporting
confidence: 57%
“…Regarding the HMDB annotation of some metabolites found in this work, B-trisaccharide is a metabolite found in a variety of animal-derived foods. A previous study has found this substance in urine after galactose administration [90], and it might also be a prebiotic (HMO) present in HM [91]. Neocasomorphin, found in our HM samples, is a casein-derived peptide with opioid function [92].…”
Section: Discussionsupporting
confidence: 57%
“… 2022 ; Selvamani et al. 2023 ). Due to the fact, that invertebrate enzymes do not need the help of the molecular chaperone Cosmc for proper folding, they may be in the future an interesting alternative for the metabolic engineering of expression systems established for the production of medically relevant oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Especially infant gut microbiota benefit from those glycans ( Zhang et al. 2022 ; Selvamani et al. 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation